IMPLEMENTASI SISTEM PEMBAYARAN PARKIR BERBASIS QRIS DI TEPI JALAN UMUM KOTA YOGYAKARTA - Ratna Devilia Putri; Cinthia Mutiara Hapsari (JMMU: JURNAL MAHASISWA MANAJEMEN DAN UMUM, 2026)
The implementation of a QR-based parking payment system improves the effectiveness and transparency of roadside parking management in Yogyakarta City. This system was implemented by the Yogyakarta City Transportation Agency as part of efforts to digitize public services and optimize regional revenue. The study used a qualitative descriptive approach, with data collection techniques through observation, interviews, and documentation. The QR-based payment system improves transparency and accountability because transactions are recorded digitally and simplifies the revenue reporting process. Parking management effectiveness has improved in terms of administration and oversight. However, the implementation of this system still faces obstacles such as low public interest in digital parking payments and limited internet access in some locations. Therefore, socialization and strengthened supervision are needed to optimize the implementation of the QR-based system.